2013
DOI: 10.1177/0956797613480803
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Memory

Abstract: Distinguishing between living (animate) and nonliving (inanimate) things is essential for survival and successful reproduction. Animacy is widely recognized as a foundational dimension, appearing early in development, but its role in remembering is currently unknown. We report two studies suggesting that animacy is a critical mnemonic dimension and is one of the most important item dimensions ultimately controlling retention. Both studies show that animate words are more likely to be recalled than inanimate wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
127
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(139 citation statements)
references
References 28 publications
11
127
1
Order By: Relevance
“…Although a great deal of research has been presented as showing a processing advantage in attention, memory, and other cognitive domains for animate compared to inanimate entities (e.g., Abrams & Christ, 2003; Bonin et al, 2013; Capitani et al, 2003; Caramazza & Mahon, 2003; Caramazza & Shelton, 1998; Gobbini et al, 2011; Johansson, 1973; Nairne et al, 2013; New et al, 2007; Pratt et al, 2010; VanArsdall et al, 2014), the current results suggest that these effects may instead be due to the ease with which an entity is perceived as an agent. Demonstrations of an advantage for processing animate versus inanimate entities have been cited as evidence for the evolutionary pruning of the human mind to adapt to the primeval challenges of survival (Nairne et al, 2013; New et al, 2007).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Although a great deal of research has been presented as showing a processing advantage in attention, memory, and other cognitive domains for animate compared to inanimate entities (e.g., Abrams & Christ, 2003; Bonin et al, 2013; Capitani et al, 2003; Caramazza & Mahon, 2003; Caramazza & Shelton, 1998; Gobbini et al, 2011; Johansson, 1973; Nairne et al, 2013; New et al, 2007; Pratt et al, 2010; VanArsdall et al, 2014), the current results suggest that these effects may instead be due to the ease with which an entity is perceived as an agent. Demonstrations of an advantage for processing animate versus inanimate entities have been cited as evidence for the evolutionary pruning of the human mind to adapt to the primeval challenges of survival (Nairne et al, 2013; New et al, 2007).…”
Section: Discussioncontrasting
confidence: 70%
“…The distinction between animate and inanimate is a critical component of semantic knowledge (Caramazza & Mahon, 2003), emerges early in development (Opfer & Gelman, 2011), and is associated with distinct patterns of brain activation (Caramazza & Shelton, 1998; Gobbini et al, 2011). Finally, words or pictures representing animate entities are better remembered than those representing inanimate entities (Bonin, Gelin, & Bugaiska, 2013; Nairne, VanArsdall, Pandeirada, Cogdill, & LeBreton, 2013; VanArsdall, Nairne, Pandeirada, & Cogdill, 2014). …”
mentioning
confidence: 99%
“…As the results indicated that participants were not better at tracking positions associated with animals but were better at remembering what they depicted, this might suggest an advantage in memory (Nairne et al., 2013, 2017) or encoding (Hagen & Laeng, 2017). Indeed, more effective encodings of animals from brief exposures (as implied by the brief target inspections occurring in such tasks, Oksama & Hyönä, 2016) might yield the indicated advantage in reporting where particular animals were localized.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the task is similar to Experiments 1 and 2, except for making the appearance of the objects at assignment directly relevant for performance. Due to the extensive literature on category-specific deficits for animals in naming, recognition and memory (e.g., Capitani et al., 1994; Låg, 2005; Låg et al., 2006; Laws & Hunter, 2006; Laws & Neve, 1999; Nairne, VanArsdall, & Cogdill, 2017; Nairne, VanArsdall, Pandeirada, Cogdill, & LeBreton, 2013), it seems difficult to purely attribute an effect of superior identity tracking accuracy for animals as stemming from an attentional bias. Consequently, we designed for the acquisition of position accuracy measures as well, by making the task sufficiently difficult, so as to avoid ceiling effects.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, VanArsdall, Nairne, Pandeirada, and Blunt (2013) and Nairne, VanArsdall, Pandeirada, Cogdill, and LeBreton (2013) have reported another type of evidence for a functional view of memory. Rather than manipulating the type of encoding, these researchers used items that varied along the animate-inanimate dimension and found that animate items were better remembered than inanimate items (see also Bonin, Gelin, & Bugaiska, in press for further evidence).…”
Section: Limitations Of the Survival Effectmentioning
confidence: 97%